Akselerasi Peran Komunikasi Keluarga melalui Aplikasi Sayurbox dalam Konten Digital Youtube - Octavia Putri Tjajadi; Rustono Farady Marta; Edo Prasetyo (Risenologi, 2021)
Fulfilling the need for food in the modern era changes as technology advances, not to mention the COVID-19 pandemic which requires that interpersonal communication be strictly avoided and/or distanced. The Sayurbox application provides a practical solution to connect buyers and sellers, whether as partners, agents, suppliers, etc. This research was presented with the aim of seeing the presence of the Sayurbox Business in accelerating in this case of family roles of Mr. Simon and Steward (a ten year old child) who has a father and son relationship. Leaning on the constructivism paradigm with a qualitative approach, Youtube Digital Content that tells the experience of the role of the family using Mayring Content Analysis Method. Results showed that Le Poire's Family Communication Role Theory which consists of two main functions can be accelerated well with the Sayurbox Application. The role of nurturing and controling occurs simultaneously in the form of carefully educating Mr. Simon as a father to the Steward as a child. The education delivered is not only verbal, but is implemented directly in the form of work in the daily life of the family.